Introduction to the statistical physics of integrable many-body systems - Samaj, Ladislav; Bajnok, Zoltan (Cambridge Cambridge University Press, 2013)
This book considers a variety of models of integrable systems and demonstrates a number of situations to which they can be applied. It includes topics not traditionally covered in literature, such as (1+1)-dimensional QFT. Suitable for graduate students and researchers in statistical physics, quantum mechanics and mathematical and theoretical physics.
Keywords: Many-body problem; Quantum theory -- Statistical methods; Statistical physics